Exploration of bifunctionality in Mn, Co Codoped CuO nanoflakes for overall water splitting - Rani, Balasubramanian Jansi (2024)
Herein, bimetal (Mn, Co) codoping on a CuO host is aimed at enhancing oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) activity. Codoping of Mn and Co on CuO to enhance bifunctional action in electrochemical water splitting has not yet been investigated to the best of our knowledge. Literatures are focused on unary Mn-doped CuO or Co-doped CuO nanostructures. Mn, Co codoped CuO through an easy chemical coprecipitation method has been successfully attempted and is more beneficial which is the novelty of the present work. Defect-enriched ample active sites (Mn2+/Mn3+ and Co2+/Co3+) along with Cu2+ in the host CuO achieved high current density (100 mA/cm2) in OER and HER with low overpotential such as 468 mV and 271 mV, respectively. Faster charge transfer and diffusion ability was stimulated by the bimetal codoping CuO. Reasonable Tafel plot values (OER: 199 mV/dec, and HER: 21 mV/dec) with improved water-splitting reaction kinetics were achieved for the Mn, Co codoped CuO nanoflakes. The double-layer capacitance ( C dl ) value of 27.5 mF/cm2 for Mn, Co codoped CuO nanoflakes was achieved. Similarly, the increasing order of an electrochemically active surface area (EASA) was exhibited by the consequent addition of bimetal doping on CuO, denoted as Mn , Co / CuO > Co / CuO > Mn / CuO > CuO . The evidence shows that the codoping strategy could facilitate rapid reaction kinetics to develop overall water splitting. The charge transfer resistances ( R ct ) of 3.6 Ω and 1.2 Ω for the Mn, Co codoped CuO nanostructure corresponding to the OER and HER, respectively, were reported. The long-term stability over 16 h with negligible loss was reported for both the OER and the HER performance. Thus, this work contributes to better insight and analysis of the successful codoping of bimetal elements in earth-abundant electrocatalysts to enhance and make practical the electrocatalytic water-splitting activity.